Genetic Studies and Backcross Breeding for Shelf Life and Yield in Long Bean (Vigna Sesquipedalis (L.) Fruw) - Rahman, Md. Anisur (1997)
A study was conducted on genetics of shelf life and yield characters of long bean. Four parental lines namely, L30, KU7, KU8 and CSL 1 9 were used in the study. Genetic component analysis for shelf life and yield characters were done following generation mean analysis from four cross combinations namely Cross 1 (L30 X KU7), Cross 2 (L30 X KU8), Cross 3 (KU7 X KU8) and Cross 4 (L30 X CSL1 9). F1, F2 and backcross generations were developed. A study was also conducted to transfer genes for long shelf life from a donor parent (L30) to the genetic background of recurrent parent (KU7, KU8, CSL 19) using backcross breeding method. Results of scaling test showed that the additive-dominance model was adequate in explaining the genetic control of seeds per pod, seed weight, pod protein and seed protein in Cross 1; pod protein, seed protein and pod protein yield per plant in Cross 2; and shelf life in Cross 4. This study revealed the importance of dominance gene effects, followed by dominance X dominance (I) interaction effects for shelf life and yield characters. The additive gene effect was proportionately small . Duplicate type of epistasis was observed in most of the characters including shelf l ife. Exploitation of heterosis breeding is suggested for the improvement of these traits having involved with non-additive gene effects. For characters which are under the control of additive (d) and additive X additive (i) gene interactions, simple selection procedu re like pedigree method in the early generation is recommended . The varied estimates of narrow-sense heritability among the crosses for different characters were due to genotype X environment interactions. Estimates of narrow-sense heritability for pod yield per plant and shelf life were high in Crosses 1 and 2, respectively. Shelf life and pod yield manifested high estimates of narrow-sense heritability in Cross 4. The degree of heterosis varied with characters among the crosses, because of diverse geographical origin of the parental lines and the contributions of background genotypes through its interaction with segregating loci. Heterosis estimates were moderately h igh for shelf life and pod yield per plant in Cross 1, and low in Crosses 2, 3 and 4. Days to flower, days to harvest, moisture content and pod length showed negative heterosis among the crosses, indicating earliness of the hybrids, having less moisture content and reduced pod length .